2009
DOI: 10.1097/rli.0b013e31818935eb
|View full text |Cite
|
Sign up to set email alerts
|

High Sensitivity

Abstract: Background The use of antiangiogenic therapy in conjunction with traditional chemotherapy is becoming increasingly in cancer management, but the optimal benefit of these targeted pharmaceuticals has been limited to a subset of the population treated. Improved imaging probes that permit sensitive detection and high-resolution characterization of tumor angiogenesis could improve patient risk-benefit stratification. Objectives The overarching objective of these experiments was to develop a dual modality αvβ3-ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(33 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…In a rabbit subcutaneous VX2 tumor model, Lijowski et al [38] found that systemically administered α v β 3 -targeted 99m Tc-gadolinium nanoparticles (270 nm in diameter) produced a higher tumor-to-muscle uptake ratio than nontargeted nanoparticles. Interestingly, we did not observe any differential uptake between PEG-HAuNS and RGD-PEG-HAuNS at any time point after IV injection, possibly because of preferential uptake of the nanoparticles in the liver’s reticuloendothelial system.…”
Section: Discussionmentioning
confidence: 99%
“…In a rabbit subcutaneous VX2 tumor model, Lijowski et al [38] found that systemically administered α v β 3 -targeted 99m Tc-gadolinium nanoparticles (270 nm in diameter) produced a higher tumor-to-muscle uptake ratio than nontargeted nanoparticles. Interestingly, we did not observe any differential uptake between PEG-HAuNS and RGD-PEG-HAuNS at any time point after IV injection, possibly because of preferential uptake of the nanoparticles in the liver’s reticuloendothelial system.…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned PET imaging with 18F-fluorodeoxyglucose ( 18 F-FDG) depicts the metabolic discrepancies between malignant and healthy cells by indicating increased glucose uptake by cancer cells. An example for a more cancer specific approach which however is also not limited to a certain type of malignancy is designing probes which attach to certain integrins which are highly expressed on tumor vascular endothelial cells, while being almost undetectable on normal blood vessels, making them a potential target for imaging during early cancer diagnosis [16-18]. Similarly, probes developed in our collaborative laboratories are targeted at extracellular matrix enzymes, specifically matrix metalloproteinases (MMPs) 2 and 9 which are expressed by a range of tumor cell lines [19-24].…”
Section: Molecular Imaging Applications In Cancer Diagnosis and Stmentioning
confidence: 99%
“…T1-based α v β 3 -targeted 99m Tc-Gd nanoparticles have been reported for SPECT-MR imaging of tumor angiogenesis. The high contrast sensitivity of SPECT enabled detection of small lesions, while the vascular-targeted MR component facilitated 3D characterization of neovasculature [149]. 111 In-perfluorocarbon nanoparticles have also been investigated as a multimodal PET-MR agent [133].…”
Section: Targeted Nanoparticle Imaging Agentsmentioning
confidence: 99%